Significant increase in prostaglandin E-major urinary metabolite with physical exercise suggesting muscle inflammation. Issue 1 (31st December 2023) - Okayasu, Isao; Kuroiwa, Hatsumi; Shinkawa, Kanako; Hayashi, Kaori; Sato, Seiichi; Iwata, Noboru; Tano, Goichi; Sekizaki, Ryo; Umeda, Kazuyuki; Ohnishi, Hiromitsu
Abstract : Introduction : Prostaglandin E-major urinary metabolite (PGE-MUM) may be a good biomarker of inflammation and useful in monitoring diseases, without the necessity of invasive sampling. To see whether inflammation in muscles occurs during physical exercise, the influence of physical exercise on urinary PGE-MUM levels was analyzed in high school boys belonging to a soccer club. Materials and methods : Void urine samples were obtained before and after physical exercises 1 (mild exercise) and 2 (repeated mild exercise). To avoid the influence of a change in urinary volume, PGE-MUM values (ng/mL) were corrected by the concentration of urinary creatinine (mg/dL) and expressed as PGE-MUM·Cr (µg/g creatinine). Urinary total protein·Cr (µg/g creatinine) and L-type fatty acid-binding protein·Cr (µg/g creatinine) (L-FABP·Cr) were compared with PGE-MUM·Cr. Results : The PGE-MUM·Cr level increased significantly immediately after playing soccer (regular 'mild' exercise) in exercise study 1 or running (repeated mild exercise) in exercise study 2, but declined the next morning. PGE-MUM (ng/mL) levels in both exercises strongly correlated (Spearman correlation coefficient, ρ = 0.728; 0.480, respectively) with urinary creatinine (mg/dL) thought to be derived from muscle exercise. Conclusion : The early increase in the PGE-MUM·Cr level just after physical exercise may reflect muscle damage and inflammation caused by the exercise.